2021
DOI: 10.1038/s41598-021-00755-z
|View full text |Cite|
|
Sign up to set email alerts
|

Link between serum lipid signature and prognostic factors in COVID-19 patients

Abstract: Although the serum lipidome is markedly affected by COVID-19, two unresolved issues remain: how the severity of the disease affects the level and the composition of serum lipids and whether serum lipidome analysis may identify specific lipids impairment linked to the patients' outcome. Sera from 49 COVID-19 patients were analyzed by untargeted lipidomics. Patients were clustered according to: inflammation (C-reactive protein), hypoxia (Horowitz Index), coagulation state (D-dimer), kidney function (creatinine) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 43 publications
8
23
3
2
Order By: Relevance
“…We found that the use of antidepressants with high FIASMA activity, comprising specific SSRI and non-SSRI molecules, was significantly less prevalent in adult inpatients who tested positive versus negative for the SARS-CoV-2 in a matched analytic sample, and significantly associated with reduced mortality. These findings are in line with prior preclinical [ 45 ] and observational [ 28 , 29 ] study results, suggesting the utility of medications with FIASMA activity against COVID-19 disease progression, as well as studies showing that plasma levels of ceramides and enzyme activities of sphingomyelinase and ceramidase strongly correlate with disease clinical severity and inflammation markers in patients with COVID-19 [ 60 , 61 , 62 , 63 , 64 ]. Inhibition of the ASM catalyzing the formation of ceramides [ 50 , 65 ] by FIASMA antidepressants may result in two effects: antiviral—through the reduced formation of ceramide-enriched membrane domains that facilitate SARS-CoV-2 entry in cells, and anti-inflammatory—through the inhibition of ASM in endothelial cells and the immune system [ 7 , 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…We found that the use of antidepressants with high FIASMA activity, comprising specific SSRI and non-SSRI molecules, was significantly less prevalent in adult inpatients who tested positive versus negative for the SARS-CoV-2 in a matched analytic sample, and significantly associated with reduced mortality. These findings are in line with prior preclinical [ 45 ] and observational [ 28 , 29 ] study results, suggesting the utility of medications with FIASMA activity against COVID-19 disease progression, as well as studies showing that plasma levels of ceramides and enzyme activities of sphingomyelinase and ceramidase strongly correlate with disease clinical severity and inflammation markers in patients with COVID-19 [ 60 , 61 , 62 , 63 , 64 ]. Inhibition of the ASM catalyzing the formation of ceramides [ 50 , 65 ] by FIASMA antidepressants may result in two effects: antiviral—through the reduced formation of ceramide-enriched membrane domains that facilitate SARS-CoV-2 entry in cells, and anti-inflammatory—through the inhibition of ASM in endothelial cells and the immune system [ 7 , 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the majority of lipids with higher levels in the plasma of SARS-CoV-2 infected patients vs. healthy control subjects were unsaturated lipids. This finding could be related to an increased level of oxidative stress in SARS-CoV-2 infected subjects as has been suggested by other metabolomic studies ( 14 , 15 ). Lipid metabolic remodeling of the host cell is a key feature of virus infection ( 22 ) and has been described and discussed for SARS-CoV-2 infection in several reviews ( 18 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 73%
“…We detected similar changes in the plasma concentration of two of these lipids in our dataset (see Figure 5 and Supplementary Figure 6 ). Dei Cas and collaborators report a correlation between lipid signatures and prognostic factors for SARS-CoV-2 infected subjects ( 14 ). Only one of the lipids described in this study was also identified in our dataset (variation illustrated in Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an observational multicenter retrospective study, use of a FIASMA medication upon hospital admission was associated with a substantially reduced risk of intubation or death [23]. Finally, plasma levels of certain sphingolipids, particularly sphingomyelins and ceramides, were found to correlate with disease clinical severity [29][30][31], inflammation markers [29,30] and viral load [30,31] in patients with COVID-19. Altogether, these data support the central role of ASM/ceramide system in SARS-CoV-2 infection that could be targeted by hydroxyzine, even if the magnitude of the in vitro FIASMA effect of this treatment (i.e., in vitro residual ASM activity of 43%) is slightly lower than that of fluoxetine (13%) and fluvoxamine (37.4%) [18].…”
Section: Introductionmentioning
confidence: 99%